2017
DOI: 10.3233/jad-160792
|View full text |Cite
|
Sign up to set email alerts
|

Do Hearing Aids Influence Behavioral and Psychological Symptoms of Dementia and Quality of Life in Hearing Impaired Alzheimer’s Disease Patients and Their Caregivers?

Abstract: These findings do not provide evidence of improvement in behavioral symptoms, functional status, or QoL of hearing impaired AD patients and their caregivers after 6 months of HA use. However, we cannot exclude that HAs may have a positive effect in patients aged less than 75 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 34 publications
0
65
0
Order By: Relevance
“…However, hearing aid use was reported to be similarly high in studies that reported using behind-the-ear style aids. Allen et al (2003), Nguyen et al (2017) and Adrait et al (2017) reported a tendency for greater improvement in hearing disability, general quality of life and cognition among those who used hearing aids more often compared to those who used them less frequently.…”
Section: Hearing Interventionsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, hearing aid use was reported to be similarly high in studies that reported using behind-the-ear style aids. Allen et al (2003), Nguyen et al (2017) and Adrait et al (2017) reported a tendency for greater improvement in hearing disability, general quality of life and cognition among those who used hearing aids more often compared to those who used them less frequently.…”
Section: Hearing Interventionsmentioning
confidence: 94%
“…All remaining studies were of low-tomoderate quality, and consisted of low-level evidence, such as single case reports, small case series or uncontrolled and underpowered treatment trials. Only five papers (Adrait et al, 2017;Hopper et al, 2016;Mamo et al, 2017;Nguyen et al, 2017;Whitson et al, 2013) The most commonly included outcome measures were hearing/vision-related disability and behavioural and psychological symptoms of dementia. Addressing sensory impairments may have additional benefits in other areas (e.g.…”
Section: Assistive Listening Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the few studies that have been conducted that assessed the cognitive abilities of adults with dementia following HA fitting, results have not shown substantial improvements in cognitive function. Nguyen and colleagues 78 and Adrait and colleagues 79 described a multicenter randomized control trial to determine if the use of HAs improves cognition and behavior in 51 individuals with probable Alzheimer's disease and hearing loss. In their companion papers, participants were randomly assigned to either active HA group or a placebo HA group for 6 months.…”
Section: Hearing Interventions For Individuals With Dementia: the Evimentioning
confidence: 99%